Political Dynasties and Legal Loopholes in Regional Elections: a Case Study of Families of Regional Officials in the 2024 Political Year - AFIF SYARIFUDIN YAHYA (Faculty of Law, Universitas Pekalongan, 2025)
The phenomenon of political dynasties in regional head elections continues to show an upward trend, especially in the lead-up to the 2024 Simultaneous Regional Elections. In an electoral democracy, the domination of power by incumbent families poses a serious threat to the principles of meritocracy, fair competition, and public accountability. The re-emergence of prominent names from the inner circles of regional political families indicates that power is no longer contested through open mechanisms, but rather inherited structurally through kinship networks and political patronage. This research employs a qualitative approach with a normative-empirical design. Data were obtained through a literature review of legislation, Constitutional Court rulings, as well as research reports and scholarly publications related to political dynasties and regional elections. The primary aim of this research is to examine the relationship between legal loopholes in regional election regulations and the rise of political dynasties, as well as their impact on the quality of democracy and local governance. The findings reveal that the absence of substantive norms limiting the candidacy of incumbent family members creates a legal gap that is exploited to perpetuate power. The annulment of Article 7 letter r of Law No. 8 of 2015 by the Constitutional Court has further legitimized political dynasties within a system that remains democratically unconsolidated. The consequences include declining leadership quality, increased conflicts of interest, weakened oversight, and a growing number of corruption cases in regions dominated by political dynasties. This phenomenon also narrows the space for political competition and strengthens the dominance of local oligarchies in electoral contests.